Preventing Foodborne Illness: E. coli O157:H7 - Keith R. Schneider; Renée M. Goodrich-Schneider; Alexandra Chang; Susanna Richardson (EDIS)
Escherichia coli is a bacterium found in the digestive system of healthy humans and animals and transmitted through fecal contamination. There are hundreds of known E. coli strains, with E. coli O157:H7 being the most recognized. This enterohemorrhagic E. coli (or EHEC) strain is responsible for an estimated 63,153 cases of infection and 20 deaths in the United States annually and causes approximately $255 million in losses each year. E. coli are found everywhere in the environment but mostly occupy animal surfaces and digestive systems, making it important to thoroughly wash anything that comes into contact with these surfaces. This 5-page fact sheet was written by Keith R. Schneider, Renée Goodrich Schneider, Alexandra Chang, and Susanna Richardson and published by the UF Department of Food Science and Human Nutrition, October 2013.